An enhanced care package to improve asthma management in Malawian children: a randomised controlled trial. Issue 5 (21st January 2021) - Rylance, Sarah; Chinoko, Beatrice; Mnesa, Bright; Jewell, Chris; Grigg, Jonathan; Mortimer, Kevin
Abstract : Background: Shortages of clinical staff make chronic asthma care challenging in low-income countries. We evaluated an outpatient asthma care package for children, including task-shifting of asthma management roles. Methods: We conducted a non-blinded individually randomised controlled trial at a tertiary-level government hospital in Blantyre, Malawi. Children aged 6–15 years diagnosed with asthma were recruited from outpatient clinic, stratified by Childhood Asthma Control Test (cACT) score and allocated 1:1 from a concealed file, accessed during electronic questionnaire completion. The intervention, delivered by non-physicians, comprised clinical assessment, optimisation of inhaled treatment, individualised asthma education. The control group received standard care from outpatient physicians. Primary outcome for intention-to-treat analysis was change in cACT score at 3 months. Secondary outcomes included asthma exacerbations requiring emergency healthcare and school absence. Findings: Between September 2018 and December 2019, 120 children (59 intervention; 61 control) were recruited; 65.8% males, with mean (SD) age 9.8 (2.8) years, mean (SD) baseline cACT 20.3 (2.6). At 3 months, intervention children (n=56) had a greater mean (SD) change in cACT score from baseline (2.7 (2.8) vs 0.6 (2.8)) compared with standard care participants (n=59); a difference of 2.1 points (95% CI: 1.1 to 3.1, p<0.001). Fewer intervention children attended emergency healthcare (7.3% vs 25.4%, p=0.02) and missed school (20.0% vs 62.7%, p<0.001) compared with standard care children. Interpretation: The intervention resulted in decreased asthma symptoms and exacerbations. Wider scale-up could present substantial benefits for asthmatic patients in resource-limited settings. Trial registration number: PACTR201807211617031.